Red Blood Cell Transfusion for Pediatric Autoimmune Hemolytic Anemia in an Emergency Situation - Murti Andriastuti; Ni Ken Ritchie; Kartika Anastasia Kosasih; Fakhri Muhammad; Anisa Dwi Fathinasari; Djajadiman Gatot (eJournal Kedokteran Indonesia, 2021)
Autoimmune hemolytic anemia (AIHA) is often presented with severe anemia. Currently, several centers in Indonesia use washed red blood cells (RBCs) to transfuse AIHA patients. However, washed RBCs are not widely available, causing a delay in therapy. We herein report two cases of pediatric AIHA who presented with severe anemia with hemoglobin level of 4.1 g/dL and 5.3 g/dL. Both patients were delayed for two and five days to be given blood transfusion because of the unavailability of washed RBC in Sorong General Hospital and Fatmawati Hospital and must wait to be referred to RSCM to receive washed RBCs. We conducted literature searches to review several articles that focus on AIHA transfusion management. AIHA is characterized by the production of autoantibodies directed against antigens on the surface of RBCs. RBC washing is not currently required in AIHA patients. It is also not widely available, takes a long time to process, and can cause a delay in emergency cases. Although RBC transfusion is not contraindicated in AIHA, its use should be limited to life-threatening cases of anemia with signs of cardiac and neurological compromises. In emergency cases, ABOmatched and Rhesus-matched RBCs can be safely administered if alloantibodies are reasonably excluded based on the previous transfusion and pregnancy history. ABO-matched and Rh-matched RBC transfusion is safe as AIHA’s transfusion management for patients with severe anemia with clinical symptoms.